The Association Between Early Graft Function, Donor Type and Long-Term Kidney Transplant Outcomes - Karthik Venkataraman; Karthik Venkataraman; Karthik Venkataraman; Georgina L. Irish; Georgina L. Irish; Georgina L. Irish; Michael G. Collins; Michael G. Collins; Michael G. Collins; Philip A. Clayton; Philip A. Clayton; Philip A. Clayton (Transplant International)
Delayed graft function (DGF), is associated with inferior graft outcomes. Whether poor graft function without dialysis, termed slow graft function (SGF), affects outcomes is unclear. We investigated associations between SGF (serum creatinine dropping by less than 30% between days 1 and 2), DGF and graft outcomes by donor type in a cohort of 17,579 Australian and New Zealand kidney transplant recipients from 2001–2021. The primary outcomes were graft survival and death-censored graft survival Compared with immediate graft function, both SGF (Adjusted hazard ratio [aHR] 1.48 (95% CI 1.14–1.91) and DGF [aHR 1.97 (1.42–2.73)] were associated with reduced graft survival in living donor and donation after brain death (DBD) recipients [SGF aHR 1.13 (1.01–1.27); DGF aHR 1.37 (1.24–1.51)]. In donation after circulatory death (DCD) recipients, DGF [(aHR 1.52 (1.13–2.04)] but not SGF [(aHR 1.55 (1.13–2.13)] was associated with reduced graft survival. Findings were similar for death-censored graft survival. In secondary analyses, SGFwas associated with reduced patient survival in living donor recipients. SGF and DGF were associated with lower 12-month eGFR for all donor types. DGF increased the odds of rejection for all donor types; for SGF this association was significant only for DBD recipients. SGF is associated with adverse outcomes in live donor and DBD kidney recipients.